A Guide for Chairs: to Encourage Undergraduate Research in Art as standard practice in the classroom. - Vaughan Judge Professor (Academic Chairpersons Conference Proceedings, 2019)
This presentation is based upon my coming book publication which I am the principle writer and coauthor with Dr. Jenny Olin Shanahan & Dr. Gregory Young. This talk starts with an overview of undergraduate research, supplies tools for scaffolding research skills, and examples of undergraduate research activities and case studies on projects in the various areas of art study. For Heads of Dept and Directors of research based education
Keywords: Research